2006
DOI: 10.1073/pnas.0507321103
|View full text |Cite
|
Sign up to set email alerts
|

A landscape effect in tenosynovial giant-cell tumor from activation of CSF1 expression by a translocation in a minority of tumor cells

Abstract: Tenosynovial giant-cell tumor (TGCT) and pigmented villonodular synovitis (PVNS) are related conditions with features of both reactive inflammatory disorders and clonal neoplastic proliferations. Chromosomal translocations involving chromosome 1p13 have been reported in both TGCT and PVNS. We confirm that translocations involving 1p13 are present in a majority of cases of TGCT and PVNS and show that CSF1 is the gene at the chromosome 1p13 breakpoint. In some cases of both TGCT and PVNS, CSF1 is fused to COL6A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
401
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 465 publications
(418 citation statements)
references
References 27 publications
12
401
0
5
Order By: Relevance
“…Cytogenetic studies of TGCTs have previously revealed that 1p11-13 is frequently involved in structural aberrations (Mertens et al, 1993;Dal Cin et al, 1994;Rowlands et al, 1994;Ohjimi et al, 1996;Sciot et al, 1999;Nilsson et al, 2002) and that 2q35-37 is the most common translocation partner of chromosome 1 (Nilsson et al, 2002). These results were confirmed in a study by West et al, (2006) that additionally identified the colony-stimulating factor-1 (CSF1 or M-CSF1) locus at 1p13 as the molecular target of the chromosomal rearrangements in 20 of 23 TGCT cases. Chromosome 2 was the translocation partner in a subset (3 of 10) of the cases and collagen type VI alpha-3 (COL6A3) was identified as the gene involved at 2q37.…”
Section: Introductionsupporting
confidence: 72%
“…Cytogenetic studies of TGCTs have previously revealed that 1p11-13 is frequently involved in structural aberrations (Mertens et al, 1993;Dal Cin et al, 1994;Rowlands et al, 1994;Ohjimi et al, 1996;Sciot et al, 1999;Nilsson et al, 2002) and that 2q35-37 is the most common translocation partner of chromosome 1 (Nilsson et al, 2002). These results were confirmed in a study by West et al, (2006) that additionally identified the colony-stimulating factor-1 (CSF1 or M-CSF1) locus at 1p13 as the molecular target of the chromosomal rearrangements in 20 of 23 TGCT cases. Chromosome 2 was the translocation partner in a subset (3 of 10) of the cases and collagen type VI alpha-3 (COL6A3) was identified as the gene involved at 2q37.…”
Section: Introductionsupporting
confidence: 72%
“…The 12 cases of giant cell tumor of tendon sheath/ diffuse-type giant cell tumor (GCTTS/DTGCT) were profiled as described previously. 5 Additional paraffin-embedded tumor samples from 26 cases of GCTOB, 25 cases of ABC, 15 cases of chondroblastomas, 12 cases of GCRG, 12 cases of chondromyxoid fibromas, 4 cases of hyperparathyroidism associated brown tumors, 4 cases of FD and 53 cases of GCTTS/DTGCT were collected from Stanford University Medical Center and Vancouver General Hospital. All cases of primary bone tumors were diagnosed by experienced subspecialty bone and soft-tissue pathologists at the respective centers and reviewed by a study pathologist (TON or RBW).…”
Section: Fresh-frozen Tumor and Paraffin-embedded Tumor Samplesmentioning
confidence: 99%
“…The gene expression profiles of the 12 GCTTS/DTGCT have been published previously. 5 The clinicopathologic features the six GCTOB, three ABC and four FD are shown in Table 1. All of these bone tumors represented primary lesions.…”
Section: Gene Expression Profiling Studymentioning
confidence: 99%
“…One such example is the COL1A-PDGFB fusion in dermatofibrosarcoma protuberans (DFSP) 35 and, more recently, the CSF1-COL6A3 fusion identified in giant cell tumor of tendon sheath. 36 The recurrent t(17;22)(q22;q13) resulting in COL1A-PDGFB fusion has been reported as a consistent finding in both DFSP and giant cell fibroblastoma, supporting the concept of a common pathogenetic entity. 35 The translocation fuses the strongly expressed collagen 1 alpha 1 (COL1A1) gene on chromosome 17 with the second exon of the platelet-derived growth factor-B (PDGFB) gene on chromosome 22.…”
Section: Pathologic and Molecular Features Of Imatinib Response And Imentioning
confidence: 85%